Microsoft Dynamics AX implementation guide : your all-in-one guide to exploring and implementing Microsoft Dynamics AX - Kasat, Yogesh; Yadav, J. J. (Professional expertise distilled., 2015)
Your all-in-one guide to exploring and implementing Microsoft Dynamics AX About This Book From project kick-off to go live and upgrade, learn what to expect in each phase of the project This book guides you through the entire journey of a Dynamics AX implementation project, helping you to avoid the common pitfalls and adapt industry knowledge and best practices for your own project This one-stop guide is packed with key tools and techniques to aid your Dynamics AX implementation Who This Book Is For This book is for IT project managers, solution architects, and consultants who are planning to implement or are in the process of implementing or upgrading Dynamics AX. To use this book, you must have a working Dynamics AX system in place and must be familiar with the basics of Dynamics AX. What You Will Learn Prepare for a great start with effective project management and planning from the beginning Gather details early using effective requirement-gathering tools and techniques Gain tools and techniques for effective infrastructure planning and hardware sizing Get to grips with integration and data migration through planning and strategy Familiarize yourself with the reporting and BI tools Master functional and technical design to customize existing features and designs in your own projects Manage your configuration and you're your configuration from one environment to another Learn industry's best practices and recommendations on customization development and performance tuning In Detail Microsoft Dynamics AX is Enterprise Resource Planning (ERP) software that supports multi-site operations across various countries, providing international processing within the company. It is an ERP solution with a lot of features and functionality, and it provides support across the fields of financial, distribution, supply chain, project, customer relationship, HR, and field service management. This book is all about simplifying the overall implementation process of Dynamics AX. The purpose of this book is to help IT managers and solution architects implement Dynamics AX to increase the success rate of Dynamics AX projects. This all-in-one guide will take you through an entire journey of a Dynamics AX implementation, ensuring you avoid commonly-made mistakes during implementation. You'll begin with the installation of Dynamics AX and the basic requirements. Then, you'll move onto data migration, reporting, functional and technical design, configuration, and per ...